Comparison of Effectiveness and Safety between Intraoperative 3D-CT-Guided and C-Arm-Guided Percutaneous Balloon Compression for Idiopathic Trigeminal Neuralgia: A Multi-Center Retrospective Study - Xiong Xiao; Zhengjun Wei; Hao Ren; Hongtao Sun; Fang Luo (Pain Research and Management)
Objectives. To compare 3D-CT-guided and C-arm-guided percutaneous balloon compression (PBC) in terms of effectiveness and safety. Methods. The medical records and follow-up data of patients with idiopathic trigeminal neuralgia who underwent 3D-CT-guided or C-arm-guided PBCs in Beijing Tiantan Hospital and the Characteristic Medical Center of the Chinese People’s Armed Police Force between February 2018 and March 2020 were retrospectively reviewed and analysed. Results. A total of 291 patients were included. Among them, 212 patients underwent PBC treatment with 3D-CT and others with C-arm. One (0.5%) patient in 3D-CT group and 4 (5.1%) patients in C-arm group failed to receive PBC treatment because of failure of foramen ovale (FO) puncture (P=0.020). Among patients with successful attempts, 5 (2.4%) patients in the 3D-CT group and 11 (14.7%) patients in the C-arm group received more than one needle pass during the procedure (P<0.001). The 3D-CT group required less time than the C-arm group for puncture (P<0.001) and for the whole operation (P<0.001). The groups shared similar initial relief rates (P=0.749) and similar recurrence-free survival during follow-ups for a median of 22 months (P=0.839). No puncture-related complications occurred in either group and the two groups had similar incidences of compression-related complications. Conclusion. 3D-CT facilitated FO puncture and improved success rate of PBC. The overall time efficiency of PBC was also increased with 3D-CT. Thus, 3D-CT is a potentially useful image guidance technology for treating idiopathic trigeminal neuralgia by PBC.